The intellectual structure of learning agility: A case study using a modified BERT model for topic modeling - Grau García, Gonzalo; Martín Rodrigo, María José; Rua Vieites, Antonio (European Public & Social Innovation Review, 2025)
Introduction: The study aims to deepen the understanding of learning agility, a relatively new construct in the field. Learning agility is essential for identifying and developing leadership talent in organizations, particularly in environments of constant change. Methodology: A thematic analysis was conducted on the titles and abstracts of 112 significant works on learning agility. The analysis utilized abstract clustering and a modified version of the BERT model for topic modeling. These influential works were identified through a prior study using bibliometric citation techniques. Results: Nine intellectual topics or patterns related to learning agility were identified, along with the influential works within each topic. The results were then compared to another intellectual structure derived from a co-citation analysis of the same set of works. Correspondences between the topics identified through both methods were established. Discussion: The comparison between topics identified through thematic analysis and co-citation analysis provides a comprehensive perspective. This integrated approach helps to advance towards a unified conceptualization of learning agility, which is essential for standardizing its measurement and application. Conclusions: The study demonstrates that combining bibliometric techniques and Natural Language Processing (NLP) facilitates academic exploration in complex research areas. This approach enables the development of more objective and reliable tools for organizations to identify and develop leadership talent.